An unnoticed twelfth-century manuscript of Arator’s Historia Apostolica, Wrocław University Library, Akc. 2018/1 - Broda, Michal (Classica et Mediaevalia, 2025)
This article concerns a hitherto unknown 12th-century manuscript containing the Historia Apostolica of Arator, a 6th-century Christian poet. The codex was donated in 2018 to the Wrocław University Library, where it was given the shelf mark Akc. 2018/1. It came to the Library badly damaged and underwent conservation treatment in the Library’s Special Collections Conservation Workshop. This paper describes the physical condition of the manuscript before and after conservation, as well as presenting its content. The manuscript has not yet been cited at all in the literature on Arator, it is not included in the list of all his manuscripts, and has not been described in any catalogue. Neither its provenance nor its fate until the 19th century, when it found its way to the book collection of professor Friedrich Haase from the University of Breslau, is known.